The orphan nuclear receptor NR0B2 could be a novel susceptibility locus associated with microsatellite‐stable, APC mutation‐negative early‐onset colorectal carcinomas with metabolic manifestation. Issue 2 (29th October 2020) - Lam, Kuen Kuen; Sethi, Raman; Tan, Grace; Tomar, Swati; Lo, Michelle; Loi, Carol; Tang, Choong Leong; Tan, Emile; Lai, Poh San; Cheah, Peh Yean
Abstract: Colorectal cancer (CRC) is a high incidence cancer and major cause of cancer mortality. Though disease‐causing tumor suppressors for major syndromes are well characterized, about 10% of CRC is familial but without mutations in known tumor suppressors. We exhaustively screened 100 polyposis families for APC germline mutations and identified 13, which are APC mutation‐negative, microsatellite‐stable (MSS), and with undetectable mutation in known tumor suppressors . Whole exome sequencing in three probands uncovered two with germline frameshift NR0B2 mutations, c.293_301delTTGGGTTGGinsAC and c.227delT. Sanger Sequencing identified a third proband with NR0B2 c.157_166delCATCGCACCT frameshift mutation. All three mutations deleted the C‐terminus activation/repression domain of NR0B2, thus are loss‐of‐function mutations . Real‐time RT‐PCR performed on tumor and matched mucosa of one patient revealed that NR0B2 downstream targets, SMAD3 was derepressed while GLI1 was downregulated in the colonic mucosa compared to healthy controls. Truncated NR0B2 molecule was predicted to have weakened binding with interacting partners SMAD3, GLI1, BCL2, and RXRα, implying perturbation of TGF‐β, Hedgehog, anti‐apoptotic and nuclear hormone receptor signaling pathways. Immunostaining also revealed nuclear retention of the most severely truncated NR0B2 molecule compared to the wildtype. Microsatellite and sequencing analysis did not detect loss of wildtype allele in probands' tumors. The patient who acquired somatic KRAS mutation progressed rapidly whist the other two patients manifested with late‐onset obesity and diabetes. We propose that haploinsufficiency of NR0B2 is associated with a novel CRC syndrome with metabolic phenotypes.